ORGANIZATIONAL AND PROFESSIONAL COMMITMENT AND THEIR EFFECT ON JOB SATISFACTION - Yulius Kurnia Susanto; Adi Hastomo (Universitas Hayam Wuruk Perbanas, 2012)
The Research on relationship between commitment and job satisfaction is an interesting topicbecause job satisfaction is as the first sign in a change of accountants who work in the registeredpublic accountants. In this study, it is proposed that motivation plays an important rolein determining the effect of organizational and professional commitment towards job satisfaction.The data were collected using questionnaires. There were 150 questionnaires distributedto the registered public accountants in Jakarta, and 112 questionnaires used for theanalysis. Data were analyzed using a two-way analysis of variance. The results show that theeffect of organizational and professional commitment towards job satisfaction was dependenttowards motivation. These results suggest that the registered public accountants should encouragepublic accountant to them keep motivated and committed to the organization andprofession. The registered public accountants must pay attention to jobs expectation of theirpublic accountants. Motivation is raising the influence of organizational and professionalcommitment on job satisfaction.